Iodine-Mediated Facile One-Pot Access to N-Aryl-2-benzoxazolamines - Nariki, Haruna; Miyamura, Takuya; Matsui, Daiki; Sonoda, Motohiro; Tanimori, Shinji (SynOpen, 2020)
Facile, iodine-mediated access to N-aryl-2-benzoxazolamines has been achieved in a one-pot manner under mild reaction conditions. Reaction of 2-aminophenols and aryl isothiocyanates afforded N-aryl-2-benzoxazolamines in the presence of molecular iodine and pyridine in tetrahydrofuran at room temperature in moderate to excellent yields.
Keywords: iodine; benzoxazolamine; one-pot synthesis; cyclodesulfurization; transition-metal-free